Manajemen Kepala Sekolah Dalam Meningkatkan Kompetensi Guru di SMP Negeri 21 Bandar Lampung Tahun Pelajaran 2023/2024 - Tanti Prihartini (Student Scientific Creativity Journal, 2024)
Competency standards are a breakthrough in the world of education in improving the quality of teachers so as to make teachers not only professional but competent in their fields. This is an implementation of the national education system law, the national standard of education (SNP), the Teacher and Lecturer Law (UUGD), which is realized in the RPP on teachers which will soon be passed. Departing from the above thinking, the author takes the title "Principal's Manajmen in Improving Teacher Competence at SMP Negeri 21 Bandar Lampung" which aims to describe teacher competence and efforts to improve it, as well as supporting and inhibiting factors in efforts to improve teacher competence at SMP Negeri 21 Bandar Lampung. In this study, there are theoretical approaches listed in chapter one and chapter two which explain the theory of efforts to improve teacher competence at SMP Negeri 21 Bandar Lampung, then in chapter three the research methods used are qualitative descriptive, and chapter four research results and exposure to research findings data, chapter five discussion or data analysis, and chapter six are conclusions and suggestions. The data that has been obtained explains that the real state of teacher competence at SMP Negeri 21 Bandar Lampung states that every aspect of competence such as pedagogic competence or teacher learning management ability is stated to be still not very masterful and still below standard, but in the aspects of evaluating learning outcomes, understanding students, and implementing educational and dialogical learning, it can be said to be good.